Helping Refugees as an Expression of Concern for Human Dignity - Łakoma, Sylwia (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
This study is an attempt to present one of the obligatory cash benefits, provided on the basis of Article 36 point 1 letter g of the Act of 12.03.2004 on social assistance (Journal of Laws of 2023, item 901, hereinafter: u.p.s.), which is a benefit to cover the costs of living and learning the Polish language by foreigners who have been granted refugee status in the Republic of Poland. Granting this assistance – within the previously agreed individual integration programme – is an expression of care for the dignity of a person in a particularly difficult life situation. This assistance makes it possible to satisfy vital human needs, at least at an elementary level. The said programme, provided it is properly developed (i.e. taking into account the individual needs, skills, abilities and predispositions of the refugee) and, if necessary, also modified on an ongoing basis (depending on the changing circumstances), and later consistently implemented – with the cooperation of the foreigner and the social worker – may in fact lead to the achievement of the set objective, i.e. integration of the refugee (art. 7(11) of the u.p.s.), and in the long run also the possibility for the refugee to independently secure nonhumiliating living conditions. This study is based on an analysis of the provisions of the Social Assistance Act, statements of doctrine and judicial decisions of administrative courts.